Squamous cell carcinoma arising in a mature cystic teratoma invading the sigmoid colon: a rare presentation. (2nd May 2015) - Gooneratne, Alena Talia; James, Alexander Owen; Gupta, Jyoti; Abdulaal, Yasser
Abstract : We discuss a rare presentation of malignant teratoma in a 63-year-old woman who was admitted to accident and emergency with abdominal distension, bloody diarrhoea and peritonitis. CT of the abdomen and pelvis showed free air in the abdomen and a gas-fluid filled cavity measuring 12×6 cm in the mid-pelvis with possible fistulation that was suspicious for malignancy. A 10×12 cm ruptured dermoid cyst was found intraoperatively, which was adherent to the bowel wall. Bulky lymph nodes were also appreciated. The surgeon suspected a metastatic malignant teratoma, and a Hartmann's procedure, total abdominal hysterectomy and bilateral salpingoopherectomy were performed with clearance of the para-aortic lymph nodes. Subsequent histological analysis revealed a squamous cell carcinoma arising from an ovarian malignant teratoma. The patient went on to have carboplatin and paclitaxel chemotherapy and is alive at 6 months follow-up.